2010
DOI: 10.1007/s11270-010-0429-6
|View full text |Cite
|
Sign up to set email alerts
|

Water Cover Technology for Reactive Tailings Management: A Case Study of Field Measurement and Model Predictions

Abstract: Environmentally safe disposal of sulfiderich reactive mine tailings is one of the major challenges facing the mining industry in Canada, Scandinavia, USA, and many other parts of the world. Placing tailings under a water cover is one of the effective methods to reduce the influx of oxygen to the tailings. Wind-induced turbulence and subsequent resuspension of the tailings, however, are major concerns with this approach. In this paper, a study of wind-induced resuspension at the Shebandowan tailings storage fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Sherriff et al (2011) showed that despite high oxidation rates and metal concentrations in tailings ponds of a copper-zinc mine in Manitoba (closed in 2002), metal concentrations in a downstream lake receiving tailings outflow water were stable indicating that the tailings management activities at that site were effective to date. Kachhwal et al (2011) also demonstrated that current water cover technologies and other tailings management efforts at a nickel-copper mining site in northwestern Ontario (closed in 1998) were effective at preventing downstream export of metals in the final effluent. Water cover technologies in rehabilitation efforts at uranium mining sites in north-central Ontario (closed as recently as the mid-1990s) have successfully reduced acid generation such that only limited effluent treatment is required for pH control and radium removal (Davé 2011).…”
Section: Prognosismentioning
confidence: 96%
“…Sherriff et al (2011) showed that despite high oxidation rates and metal concentrations in tailings ponds of a copper-zinc mine in Manitoba (closed in 2002), metal concentrations in a downstream lake receiving tailings outflow water were stable indicating that the tailings management activities at that site were effective to date. Kachhwal et al (2011) also demonstrated that current water cover technologies and other tailings management efforts at a nickel-copper mining site in northwestern Ontario (closed in 1998) were effective at preventing downstream export of metals in the final effluent. Water cover technologies in rehabilitation efforts at uranium mining sites in north-central Ontario (closed as recently as the mid-1990s) have successfully reduced acid generation such that only limited effluent treatment is required for pH control and radium removal (Davé 2011).…”
Section: Prognosismentioning
confidence: 96%